1991
DOI: 10.1148/radiology.180.1.2052706
|View full text |Cite
|
Sign up to set email alerts
|

Transverse geniculate ligament of the knee: appearance at plain radiography.

Abstract: Visualization of the transverse geniculate ligament of the knee in four patients is described. This normal variant was seen on lateral plain radiographs as a small, rounded opacity surrounded by fatty tissue and located anterior to the knee joint. Magnetic resonance imaging helped confirm this image to be that of the transverse geniculate ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Several cadaveric and imaging studies of this ligament have been made and it has been shown to be of variable thickness when present [4,5,6,7,8,9]. In a recent cadaveric study, three distinct types of AIL were described with regard to its insertion on or near the anterior horns of the menisci [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several cadaveric and imaging studies of this ligament have been made and it has been shown to be of variable thickness when present [4,5,6,7,8,9]. In a recent cadaveric study, three distinct types of AIL were described with regard to its insertion on or near the anterior horns of the menisci [4].…”
mentioning
confidence: 99%
“…The AIL can sometimes be depicted in a lateral knee radiograph when there is enough surrounding fat to create adequate contrast around it [7,8]; however, it is with MR imaging that the AIL can best be visualized non-invasively. When present, this ligament is usually seen easily in the anterior part of the knee joint as a lowintensity band in MR imaging examinations of the knee [8,9].…”
mentioning
confidence: 99%
“…19C). The ligament is of variable size, and is seen in over three-fourths of knee MR examinations [71]. …”
Section: Transverse Geniculate Ligamentmentioning
confidence: 99%
“…They found that the course of the transverse geniculate ligament simulated a tear of the anterior horn of the lateral meniscus on 44 (22%) of the cases; however, no tear was found in the 9 patients who had an arthroscopic examination. In another study Sintzoff et al [5] reported the visualization of the transverse geniculate ligament on lateral plain radiography in four patients. They described the ligament as a small, rounded opacity surrounded by fatty tissue and located anterior to the knee joint.…”
Section: Introductionmentioning
confidence: 98%
“…This structure is also called the transverse geniculate ligament, meniscomeniscal ligament, anterior transverse ligament, and intermeniscal ligament. There have been a few studies considering its properties on plain radiography and on magnetic resonance imaging (MRI) [5,6,8]. Watanabe et al [8] retrospectively reviewed sagittal MRI findings of 200 knees to determine the frequency with which normal ligamentous and tendinous structures mimic pathological changes within the knee.…”
Section: Introductionmentioning
confidence: 99%